The Bearing and Breakage Characteristics of Crushed Stone Aggregates in the Bedding Course of Permeable Roads - Zhongbing Cai; Chengchun Qiu (Advances in Civil Engineering)
The current study of permeable roads helps address urban flooding in Chinese cities caused by frequent heavy rainfall and build smart cities with sponge-like functionality. Crushed stone is widely used in constructing the bedding course of permeable roads because it has good water permeability. Experiments on the compaction of crushed stone were carried out by considering the impact of particle size and gradation to examine the strength and particle breakage characteristics of crushed stone and evaluate its use as the aggregate in the bedding course of permeable roads. The compaction process can be divided into two stages, i.e., the preliminary compaction stage and the particle crushing and intensive compaction stage. The latter consists of an alternating cycle of compacting and crushing. The particle size distribution after crushing can be described analogously to the Talbot continuous gradation equation. Single particle size samples are subject to earlier and stronger particle breakage than the mixed particle size sample, which are affected by both compaction level and loading speed. This study has important application value, and it provides experimental support for the study of materials for urban permeable roads.